Stepwise isothermal fast pyrolysis (SIFP). Part II. SIFP of peanut shells – Antifungal properties of phenolic fractions - Lopez Rivilli, Patricia Virginia (2012)
Pyrolysis of peanut shells was carried out using stepwise isothermal fast pyrolysis (SIFP). SIFP consists of successive isothermal fast pyrolysis reactions, where solid products obtained in the previous isothermal fast pyrolysis become the substrate of the subsequent reaction at a higher temperature. This article reports results obtained from SIFP of peanut shells between 200 and 300°C using 100°C intervals under vacuum (0.2 mm). The maximum yield of liquid products was obtained at 300°C, giving around 30% of bio-oil, which contained mainly phenols and furan derivatives. On the other hand, since previous papers have reported fungicidal activity of phenols derivatives from lingo-cellulosic biomass pyrolysis, we carried out antifungal activity tests of bio oil obtained from peanut shells SIFT at 300 °C. Results seem promising, at least on Sclerotium rolfsii.